Sistem Informasi Hasil Pertanian Padi Pada Dinas Pertanian Kutacane - Ade Talmuji (Forum Kerjasama Pendidikan Tinggi (FKPT), 2019)
The use of technology as a support in processing data and information has become the need of every company and government agency so that the information needed can be obtained quickly and accurately in handling agricultural products both received and sent to avoid mistakes that occur. The data processing process of agricultural product information systems manually and implemented by the Agriculture Office of Kutacane takes longer and the information generated is very simple. For this reason, the author tries to design a computerized system in the agricultural service using the Visual Basic NET 2008 programming language and in processing its database using MYSQL